하수처리수의 농업용수 재이용에 따른 벼의 미질특성 분석 - 정기웅; 김학관; 장태일; 김상민; 박승우; Ki-Woong Jung; Hak-Kwan Kim; Tae-Il Jang; Sang-Min Kim; Seung-Woo Park (농업생명과학연구, 2010)
본 연구는 하수처리수의 농업용수 재이용에 따른 벼의 미질특성을 파악하기 위하여 시험포장을 조성 하여 쌀의 아밀로스 및 단백질 함량, 완전미 도정수율을 분석하고 유의성을 고찰하였다. 시험포장의 수 질 및 토양환경을 조사하였으며, 근적외선 분광분석법을 통해 미질 특성을 분석하였다. 하수처리수로 재 배된 쌀의 미질 특성치는 일반미와 큰 차이가 나지 않는 것으로 나타났으며, 통계분석 결과 5% 유의수 준에서 각 처리구별 유의차가 있는 것으로 나타났다. This study assess the effects of reclaimed wastewater irrigation on grain quality-related properties of milled rice. To conduct the effects of wastewater reuse on rice quality, the contents of amylose, protein, and milled head rice recovery were analyzed. The water and the soil quality were monitored, and the grain characteristic was analyzed using a NIRS (Near Infra-Red Spectroscopy). The value of the grain properties of the rice which was cultivated with the reclaimed wastewater didn't show a big difference from other common rice. The significant difference by each processing distinction was shown at the significance level of 5% in the statistical result.